1988
DOI: 10.1067/mva.1988.avs0070785
|View full text |Cite
|
Sign up to set email alerts
|

Bypass grafts to the ankle and foot

Abstract: Two hundred forty-three bypasses to paramalleolar arteries were performed in 224 extremities of 208 patients since 1971; 166 were implanted in men (68%) and 77 in women (32%). The median age was 73 years. Gangrene (61%), nonhealing ulcer (15%), rest pain (22%), and trauma (2%) were the indications for bypass. Usual risk factors were noted: diabetes (65%), smoking (51%), heart disease (46%), and hypertension (45%). The extent of occlusive disease dictated three graft configurations: long grafts originating in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…5,6,14,16 Although the present results for secondary patency are worse than those reported by Ascer et al 5 and Andros et al, 6 a 3-year limb salvage rate of 69% is considered satisfactory. In their study, there was a predominance of diabetes mellitus as the main associated disease.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…5,6,14,16 Although the present results for secondary patency are worse than those reported by Ascer et al 5 and Andros et al, 6 a 3-year limb salvage rate of 69% is considered satisfactory. In their study, there was a predominance of diabetes mellitus as the main associated disease.…”
Section: Discussioncontrasting
confidence: 72%
“…2-4 These major arteries are sometimes occluded, but the branches (tarsal and plantar arteries) are patent and serve as runoffs for a bypass graft. 5,6 This an exceptional technique applicable to special conditions as a last attempt for limb salvage.Technical improvements in endovascular surgery have made this method feasible for many patients. It has been used as the initial approach to CLI treatment because of its low morbidity; however, the Bypass Versus Angioplasty in Severe Ischemia of the Leg (BASIL) trial reported better results for limb salvage and long-term survival in patients treated with bypass graft surgery, 7 and there are isolated reports of angioplasty performed on pedal arteries.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…(2) Small skin incisions have caused no problems with postoperative healing. (3) It is easy to locate competent or nondisrupted valves, perforators, and branches. (4) There is a decreased rate of AV fistulas after in-situ vein bypass graft.…”
Section: Discussionmentioning
confidence: 99%
“…More distal inflow sites provide durable inflow (13,14). Likewise, more proximal outflow is associated with durable patency when there is no significant obstruction between the distal anastomosis and the arterial segment leading to the foot.…”
Section: Infra-inguinal Bypassmentioning
confidence: 96%